FEATURES SPEECH REHABILITATION IN THE ACUTE STROKE IN DIFFERENT FORMS OF APHASIA - Марина Николаевна Сафронова; Андрей Владимирович Коваленко; Ольга Александровна Мизюркина; Станислав Борисович Тен (Медицина в Кузбассе, 2018)
Objective. To determine the dependence of speech recovery on the type of aphasia, localization of the focus of ischemia and vascular risk factors in patients with acute ischemic stroke in the carotid basin.